The Relationship Between the Digital Competence of Nurses with the Quality of Nursing Care at RSUP Dr. M. Djamil Padang Year 2025 - Romliyadi (CV. Get Press Indonesia, 2026)
The development of information technology requires adequate digital competence among nurses to improve the quality of health services. However, disparities in understanding and applying digital technology persist, affecting the quality of nursing care. Therefore, evaluating nurses’ digital competence is necessary to identify barriers and develop improvement strategies. This study aimed to analyze the relationship between nurses’ digital competence and the quality of nursing care at RSUP Dr. M. Djamil Padang in 2025. This study used a quantitative design with a cross-sectional approach. The research involved 100 nurses selected through proportionate stratified random sampling. Data were collected using structured questionnaires, which had been tested for validity and reliability to measure digital competence, and observation sheets to assess the quality of nursing care. Data analysis included univariate analysis to describe frequency distributions and bivariate analysis using the chi-square test, along with odds ratio (OR) calculations. The results showed that 56% of nurses had good digital competence, while 60% demonstrated good quality of nursing care. Bivariate analysis revealed a significant relationship between digital competence and nursing care quality (p-value = 0.003; OR = 2.95). Nurses with good digital competence were 2.95 times more likely to provide high-quality care. In conclusion, digital competence is significantly associated with nursing care quality, highlighting the need for continuous training, system optimization, and technology-based policies.